Community-Acquired Pneumonia in Children: Current Approaches to the Duration of Antibiotic Therapy - S.O. Mokiia-Serbina; T.V. Litvinova; H.O. Plokhinov (Zaslavsky O.Yu., 2016)
Antibiotic therapy is recognized as the only scientifically valid method for the treatment of pneumonia, the outcome of which depends on proper antibiotic and the optimal duration of its administration that ensures the achievement of microbial eradication. The article discusses the duration of antibiotic therapy in uncomplicated community-acquired pneumonia in children. There was a trend to a reduction in the duration of antibiotic use, even with severe cases of the disease course. It is shown that currently there is no serious evidence base that would reliably show the enough duration of 5-day course of antibiotic therapy. It is proposed to consider 7-10 day course of treatment as the optimal duration of effective therapy for uncomplicated pneumonia. Implementation of the concept of short courses of antibiotic therapy is possible only under the supervision of the procalcitonin level.